Influence of Heavy Metals (Ni, Cu, and Zn) on Nitro-Oxidative Stress Responses, Proteome Regulation and Allergen Production in Basil (Ocimum basilicum L.) Plants - Georgiadou, Egli C.; Kowalska, Ewa; Patla, Katarzyna; Kulbat, Kamila; Smolińska, Beata; Leszczyńska, Joanna; Fotopoulos, Vasileios (Frontiers in Plant Science, 2018)
One of the most significant biosphere contamination problems worldwide is derived from heavy metals. Heavy metals can be highly reactive and toxic according to their oxidation levels. Their toxic effects are associated with the increased production of reactive oxygen species (ROS) and cellular damage induced in plants. The present study focuses on the effects of nickel (Ni), copper (Cu) and zinc (Zn) applied to the soil on the antioxidant response and allergen production in the aromatic plant basil (Ocimum basilicum L.) following a combined physiological, biochemical and analytical approach. The concentrations used for the three heavy metals were based on the 2002 Regulation of the Polish Ministry of the Environment on Soil Quality Standards (i. agricultural land (group B): Ni 100 ppm, Ni 210 ppm, Cu 200 ppm, Cu 500 ppm, Zn 720 ppm and ii. industrial land (group C): Ni 500 ppm, Cu 1000 ppm, Zn 1500 ppm, Zn 3000 ppm). The highest physiological and cellular damage in basil plants was caused by Cu and Zn. Increasing concentrations of Cu resulted in a further increase in cellular damage and nitro-oxidative stress, correlating with an induction in activity of reactive oxygen and nitrogen species metabolism enzymes (SOD, CAT, APX, NR). Treatment with Cu led to increased concentration of the allergenic protein profilin, while increasing concentrations of Cu and Zn led to a decrease in the concentration of total proteins (likely due to proteolysis) and antioxidant capacity. Interestingly, severe Cu stress resulted in the accumulation of specific proteins related to transpiration and photosynthetic processes. On the basis of these findings, Ni stress in basil plants appears to be less damaging and with lower allergenic potential compared with Cu and Zn stress, while Cu-stressed basil plants experience most detrimental effects and display highest allergen production.